Digital watermarking : an overview - Khalifa, Othman Omran; Yusof, Yusnita (IIUM Press, 2011)
Digital watermarking has been inspired from security concerns over multimedia contents due to the advances of computer technology. Nowadays, it is easy to obtain, manipulate, distribute and store these contents due to evolution of Internet, excellent multimedia tools and low-cost storage devices. Research community and industry has shown extensive interests in developing and implementing possible solutions via digital watermarking. Digital watermarking can be defined as the process of embedding a certain piece of information (technically known as watermark) into multimedia content including text documents, images, audio or video streams, where the watermark can be detected or extracted later to make an assertion about the data [1]. A generalized watermark model consists of watermark encoding and detection processes as shown in Figure 14.1 and Figure 14.2 [2]. The inputs to the embedding process are the watern1ark, the cover object and a secret key. The key is used to enforce security and to protect the watermark. The output of the watermarking scheme is the watermarked data. The channel for the watermarked data could be a lossy, noisy, unreliable channel. Thus the received data may be different from the original watermarked data. The inputs for extraction are the received watermarked data and the key corresponding to the embedding key. The output of the watermark recovery process is the recovered wat